Application of Exogenous Phytohormones at Silking Stage Improve Grain Quality under Post-Silking Drought Stress in Waxy Maize - Longfei Wang; Yini Yan; Weiping Lu; Dalei Lu (Plants, 2020)
The application of exogenous plant growth regulator can improve plant resistance to drought stress. The effects of application of exogenous cytokinin (CTK), brassinolide (BR), or gibberellic acid (GA) at the silking time on the grain quality of two waxy maize hybrids under drought stress at grain formation stage were studied. Grain weight of both hybrids was unaffected by exogenous phytohormones under control conditions but increased under drought conditions with the application of BR. The grain starch content in response to drought varied with hybrid and phytohormone. Starch granule size and protein content in grains were increased by drought under all conditions, but various phytohormones exerted different forms of influence. The starch λmax in Yunuo7 was unaffected by single or interaction of phytohormones and water deficit, λmax in Jingkenuo2000 with BR was unaffected but with CTK or GA increased by drought. Relative crystallinity was reduced by drought without the application of phytohormone, but with phytohormones in response to drought it was different. Flour peak viscosity was reduced by drought. The value was increased with BR spraying under control and drought conditions. Retrogradation percentage under drought conditions was unaffected by exogenous phytohormones in Jingkenuo2000. In Yunuo7, retrogradation percentage was unaffected by BR but reduced by CTK and GA. In conclusion, spraying phytohormones at the silking stage can affect grain weight and starch quality, grains with a sticky taste can be improved by applying BR, and grains with low retrograde tendency can be produced by applying CTK.